2011
DOI: 10.1111/j.1463-1318.2010.02511.x
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery for recurrent ileocolic Crohn’s disease is as safe and effective as primary resection

Abstract: Laparoscopic surgery for recurrent ileocolic Crohn's disease is safe and can lead to significant short-term benefit, including earlier discharge. Conversion increases the length of stay in hospital and the overall morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 29 publications
2
36
1
2
Order By: Relevance
“…46 Two later studies compared the results of primary and recurring Crohn's disease managed using a laparoscopic approach, and did not observe any increased morbidity or conversion rate in patients with recurrent disease. 47,48 Whether a laparoscopic approach should be pro posed in patients with recurrent disease, irrespective of the surgical approach used for the index procedure, remains controversial. Indeed, although we reported that a laparoscopic approach did not impair post operative outcomes in patients who had undergone a prior open procedure, 49 Aytac et al 50 suggested that the benefits of a laparoscopic approach in terms of post operative recovery were not maintained in patients after a midline laparotomy.…”
Section: Recurrent Crohn's Diseasementioning
confidence: 99%
“…46 Two later studies compared the results of primary and recurring Crohn's disease managed using a laparoscopic approach, and did not observe any increased morbidity or conversion rate in patients with recurrent disease. 47,48 Whether a laparoscopic approach should be pro posed in patients with recurrent disease, irrespective of the surgical approach used for the index procedure, remains controversial. Indeed, although we reported that a laparoscopic approach did not impair post operative outcomes in patients who had undergone a prior open procedure, 49 Aytac et al 50 suggested that the benefits of a laparoscopic approach in terms of post operative recovery were not maintained in patients after a midline laparotomy.…”
Section: Recurrent Crohn's Diseasementioning
confidence: 99%
“…We also employ the technique for Hartmann ' s reversal and selected cases of abdominoperineal excision of rectum [50] . Similarly, we have used the SILS technique for numerous indications, including cancer, complicated diverticular disease, ulcerative colitis, and Crohn ' s disease (including re -dos) [51] . The cohort of cancer patients we have performed SILS for includes all Dukes ' stages A -D and all tumor stages T 1 -T 4b .…”
Section: Single -P Ort L Aparoscopic C Olorectal S Urgerymentioning
confidence: 99%
“…These developments and the absolute comparability of the laparoscopic approach in complex patients with Crohn's disease was also shown by several other study groups. [15][16][17][18][19][20][21] Complex cases were defined as fistulous courses with intra-abdominal abscess or fistula and recurrent disease. 15 A meta-analysis of the aforementioned studies has shown that the laparoscopic approach could be performed on patients with fistulous and recurrent disease as well as on patients with prior surgery with potential intra-abdominal adhesions.…”
Section: Discussionmentioning
confidence: 99%